Polish question in a representative of organizations (1914-1916) - Uliana Klymiuk (Cхід, 2013)
In this paper the activity of a representative of Polish political organizations that operated in Galicia during First World War. Examined the political conditions of formation of these organizations, the purpose of their activities, ideological beliefs, political composition and attitude to the idea of Polish independence